Development and cross-validation of LMS-based normative reference standards and health benefits zones for muscular strength among adolescents by age and sex - Yang Yang; Syed Ghufran Hadier; Syed Ghufran Hadier; Liu Long; Syed Muhammad Zeeshan Haider Hamdani; Syed Muhammad Zeeshan Haider Hamdani; Syed Danish Hamdani (Frontiers in Public Health)
ObjectiveThis study aims to develop and validate age- and sex-specific normative reference standards for muscular strength (MS) using the LMS (Lambda–Mu–Sigma) method and to establish Health Benefit Zones (HBZs) for Pakistani adolescents aged 12–16 years.MethodsA cross-sectional study was conducted with 2,970 adolescents (49.7% boys, 50.3% girls) selected through stratified random sampling from 60 public high schools across three divisions of South Punjab. Anthropometric indicators and muscular strength were measured following standardized protocols. Using the LMS, age- and sex-specific normative reference values and smoothed percentile curves (3rd, 10th, 35th, 50th, 65th, and 90th) were developed. Five Health Benefit Zones (Very Poor, Poor, Medium, Good, and Excellent) were derived from these percentile ranges to classify strength levels. The robustness of the generated standards was examined through internal cross-validation using a back-generation procedure to confirm high predictive accuracy.ResultsBoys demonstrated significantly higher muscular strength than girls across all ages (p < 0.001), with strength increasing progressively with age in both sexes. At age 16, median MS reached 35.47 kg for boys and 20.18 kg for girls. LMS-derived percentile reference values and percentile curves illustrated consistent age- and sex-related growth trends. Approximately 40% of participants fell within the “poor” or “very poor” HBZs. MAPE values remained below ±0.05, indicating excellent model fit. Compared to international benchmarks, adolescents from South Punjab exhibited lower MS values across corresponding age groups.ConclusionThis study provides the first LMS-based, age- and sex-specific normative reference standards and HBZs for muscular strength among Pakistani adolescents. These standards offer a population-relevant tool for fitness assessment, enable early identification of youth at risk of low muscular strength, and support targeted interventions to enhance strength development and overall physical health in school-aged populations.